Carbon Emission Disclosure in Indonesian Firms: The Test of Media-exposure Moderating Effects - Abdullah, Muhammad Wahyuddin; Musriani, Rika; Syariati, Alim; Hanafie, Hadriana (International Journal of Energy Economics and Policy, 2020)
Carbon emission disclosure serves to justify firms’ sustainable business endeavors. This study contributes to the minor discussions of this topic in the context of Indonesian. The role of media exposure to moderate the firms’ size, profitability, leverage, and environmental performance toward carbon emission uses is also inadequately addressed in previous studies. This study aims to fill these discrepancies by investigating financial statement data of firms listed in the Jakarta Islamic Index, Indonesia (JII), from 2012 to 2016, employing moderated regression techniques. All direct relationships are significant. The media exposure significantly moderates firms’ size and leverage, but not to profitability and environmental performance. We also discuss several considerations with environmental disclosure issues in Islamic Index along with its implications. Keywords: Carbon Emission Disclosure, Firms’ Size, Leverage, Environmental Performance, Media Exposure. JEL Classifications: L82, F64, G10 DOI: https://doi.org/10.32479/ijeep.10142